HABITUASI REMAJA PECANDU NARKOBA PADA YAYASAN REHABILITASI DHIRA SUMAN TRITOHA - Vini, Dwi Yuniar; Soetrisnaadisendjaja, Denny; Widiansyah, Subhan (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Social deviations against adolescents are increasingly prevalent because of their curiosity to find identity so that for those who have the wrong association, it will have an impact on social deviations and become drug addicts. While drugs are increasing, there are not many people around to suggest addicts to rehabilitation. This study aims to identify and describe the habituation process of adolescent drug addicts at the stage of Mental, Narcotics, and Geriatrics rehabilitation at the Dhira Suman Tritoha Foundation. This study uses descriptive qualitative research methods, observation, interviews, and documentation techniques. The results of the research in this matter were analyzed using Pierre Bordieu"™s theory of Cultural Reproduction, showing that the Dhira Suman Tritoha rehabilitation foundation played a role in shaping the character of adolescent drug addicts through four aspects, namely (1) habitus: adaption of adolescent former drug addicts, (2) capital: there are four, namely economic capital (rehabilitation costs borne by parents of drug-addicted adolescent patients, social capital (establishment of the closeness of a relationship with one another in rehabilitation foundation), cultural capital (habituation in behavior is formed well), symbolic capital (providing self-control to adolescent addicted patients). (3) Arena: a form of struggle for drug addicts to recover, (4) Symbolic Violence: formation of the character of former drug addicts through control. Adolescent drug addicts during rehabilitation form good character and understanding of social norms.